Role of immunological disorders, endothelial dysfunction and hemostatic disorders in the genesis of arterial hypertension in the metabolic syndrome - E. I. Polozova; E. V. Puzanova; A. A. Seskina (Медицинская иммунология, 2020)
Mortality from diseases of the circulatory system is a challenge for the modern health care. Arterial hypertension (AH) mostly contributes to development of cardiovascular complications. It often proceeds against the background of metabolic disorders. Pathogenesis of hypertension is currently being considered a multifactorial disease. Pathogenesis of hypertension certainly has distinct features in presence of metabolic disorders,. Therefore, it is relevant to summarize current literature on the role of immunological disorders, endothelial dysfunction and hemostatic disorders in AH genesis during metabolic syndrome (MS). Most authors agree with existence of several mechanisms that determine relationships between AH and insulin resistance. Development of hypertension in MS patients with is a consequence of immunometabolic processes. Abdominal obesity is an important component of MS. It is associated with chronic inflammation of visceral adipose tissue, its excessive infiltration by immune cells, and increased production of adipokines and cytokines (TNFα, IL-6) with hypertension. AH is associated with a significant increase in T cells, that mediate endothelial dysfunction (ED) and provide a link between hypertension and subsequent atherosclerosis. T lymphocytes trigger a cascade of reactions. IL-17 is the end product of these events It is involved not only in increasing blood pressure, but also contributes to the development of vascular wall stiffness in АН patients. Thus, the relationship between several types of immune cells leads to inflammatory reactions, including those of vascular wall, initiating endothelial dysfunction. Chronic non-specific inflammation in MS, supported by the cytokine system, is a triggering mechanism for ED progression. Excessive production of endothelin-1 and inhibition of nitric oxide production are the classic markers of ED. Immune damage leads to imbalance in the production of vasoconstrictor and vasodilating substances, proliferative and antiproliferative factors in endothelium. It was shown that ED is an integral aspect of the insulin resistance syndrome in pathogenesis of arterial hypertension associated with metabolic disorders, and contributes to its worsening, increased vascular reactivity and further AH development. According to modern studies, it has been shown that excessive synthesis of pro-inflammatory cytokines introduces disturbances in the system of vascular hemostasis. When studying the effects of metabolic disorders upon hemostatic system, we may conclude that activation of fibrinolytic and plasma chains occurs in the same way for both men and women, with small gender characteristics of individual components. The rheological properties of the blood are also changed with developing MS. Systematization of the available literature data on the issue under study can serve as a basis for determining prognostic criteria of hypertension progression and risk of thrombotic complications.